Les rituels en question dans la relation éducative : rupture des liens, maintien du lien, instauration de nouveaux liens - Christiane Montandon (Nantes Université, 2015)
The contemporary deritualization, correlative to a progressively more individualized social act, highlights the embrittlement of the social link within educational institutions. Thus, devices used in greeting or accompaniment, that can be interpreted as ersatz rituals, are established. They are as much mediating, giving the establishments a foundation of fixed bearings, facilitating the inscription of each individual in the working collective. This static conception of the ritual, anchoring individual conducts into an institutionalized social space, is opposed to a dynamic conception of the ritualization process where an habitus is implemented, expected behaviors, taking on roles according to a framework. Two properties are essential in such a process: mimetic capacity and performativity. The paradoxal structure of this new paradigm is in fact its dynamic character, articulating permanence and change, as well as evolution despite and thanks to the stability of fixed bearings.